Education in the system of today’s employee values; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Makasheva N. P. Nataliya Petrovna; Ishchuk (Ishuk) T. L. Tatiana Leonidovna; Makasheva Yu. S. Yuliya Sergeevna; Kalashnikova D. S. (Petroleum Engineering Economics and Mining Law, 2016)
Title screen